Cardiovascular clinical trials : putting the evidence into practice - Flather, M.; Bhatt, Deepak L.; Geisler, Tobias (BMJ books., 2012)
The pace of therapeutic advances in the treatment of cardiovascular diseases is rapid, and new clinically-relevant information appears with such frequency that it can be extremely challenging for clinicians to keep up. Still, knowledge and interpretation of major clinical trials is crucial for the range of clinicians who manage cardiovascular patients, especially since important trial evidence often needs to be implemented soon after it is published. Confidently apply gold standard treatment for 10 of the most critical areas of cardiology Written by an international team of experts, Cardiov.